Gambaran Kejadian dan Manajemen Penatalaksanaan Dismenorea Primer Pada Mahasiswa Coas Fakultas Kedokteran Gigi - Ayu Rosita Dewi; Dika Yanuar Frafitasari; Pety Merita Sari (Journal of Pharmaceutical and Health Research, 2023)
Dysmenorrhea is pain that occurs before or during the menstrual cycle and is a gynecological problem in most adolescents. Dysmenorrhea is characterized by pain or cramps in the lower abdomen, the back, and the legs. To overcome the symptoms of dysmenorrhea, one can do so pharmacologically, non-pharmacologically, or in combination. The purpose of this study was to describe the incidence of primary dysmenorrhea and its management in students of the Faculty of Dentistry at the Bhakti Wiyata Institute of Health Sciences. This type of research is called descriptive research. Sampling technique using total sampling The population used in this study was new students in the odd semester 2022–2023 of the dental professional education program, with as many as 45 respondents. Methods of data collection using a questionnaire The results of this study described female students experiencing dysmenorrhea with mild pain intensity in 14 respondents (31%), moderate pain in 19 respondents (42%), and severe pain in 12 respondents (27%). Management of dysmenorrhea included 31 non-pharmacological respondents (69%), 4 pharmacological respondents (9%), and 10 respondents (22%), who used a combination of pharmacological and non-pharmacological methods. From the results of this study, researchers suggest female students who experience dysmenorrhea with moderate to severe pain levels see a doctor or health service and increase attention to reproductive health problems by seeking many sources of information related to the management of dysmenorrhea.